2021
DOI: 10.1037/apl0000934
|View full text |Cite
|
Sign up to set email alerts
|

Work as replenishment or responsibility? Moderating effects of occupational calling on the within-person relationship between COVID-19 news consumption and work engagement.

Abstract: As the result of the novel coronavirus (COVID-19), individuals have been inundated with constant negative news related to the pandemic. However, limited research examines how such news consumption impacts employees' work lives, including their ability to remain engaged with their work. Integrating conservation of resources theory and insights from the media psychology literature with research on occupational calling, we propose that weekly COVID-related news consumption heightens employees' anxiety levels, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 39 publications
1
30
2
1
Order By: Relevance
“…, 2020; Wrzesniewski and Dutton, 2001). Similarly, the study found a significant impact of work orientation (calling) on the adaptability of service offering, supported (H6) (Andel et al. , 2021; Wrzesniewski and Dutton, 2001; Wrzesniewski et al.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…, 2020; Wrzesniewski and Dutton, 2001). Similarly, the study found a significant impact of work orientation (calling) on the adaptability of service offering, supported (H6) (Andel et al. , 2021; Wrzesniewski and Dutton, 2001; Wrzesniewski et al.…”
Section: Discussionsupporting
confidence: 57%
“…, 1997). Researchers have been calling for increased efforts to understand the significance of work meaning due to its implications for individual and organisational outcomes (Andel et al. , 2021; Dik and Duffy, 2007).…”
Section: The Adaptability Of Service Offeringmentioning
confidence: 99%
See 1 more Smart Citation
“…In this same research, work engagement of new hires was more pronounced in regions that had implemented more robust COVID‐19 policies, indicating that a more favorable external environment during the crisis helped to contribute to individuals' engagement at work. In this context, Andel et al (2021) explored how COVID‐19‐related news consumption impacted employees' work engagement during the crisis. The authors found that COVID‐19‐related news consumption overall reduced work engagement by heightening employees' anxiety levels.…”
Section: Setting the Scene: What Have We Learned About Organizational...mentioning
confidence: 99%
“…Finally, our paper adds to conceptual work ( Akkermans et al, 2020 ; Autin et al, 2020 ; Cho, 2020 ; Spurk & Straub, 2020 ) and to empirical papers ( Andel et al, 2021 ; Lin et al, 2021 ; Trougakos et al, 2020 ) on the career- and work-related outcomes of the pandemic. Our results reveal that the pandemic blends concerns about security, work-life balance, and health, and makes these career orientations more salient for employees than those related to the job content.…”
Section: Introductionmentioning
confidence: 99%